2017
DOI: 10.1111/bcp.13247
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the predictive validity of laser‐EPs in normal, UVB‐inflamed and capsaicin‐irritated skin with four analgesic compounds in healthy volunteers

Abstract: LEP algesimetry is sensitive to analgesics with different modes of action and may enable the effects of novel analgesics to be assessed during early clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
5
16
1
Order By: Relevance
“…The significant difference from placebo was also observed in the VAS postlaser pain results, and both LEP and VAS pain results were sustained up to the end of the daily experimental observation period. The LEP N2-P2 PtP profile of pregabalin in this study was similar to previous data in healthy subjects that showed reductions in PtP amplitudes of LEPs starting one to two hours postadministration and maintained for more than six hours postdose [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The significant difference from placebo was also observed in the VAS postlaser pain results, and both LEP and VAS pain results were sustained up to the end of the daily experimental observation period. The LEP N2-P2 PtP profile of pregabalin in this study was similar to previous data in healthy subjects that showed reductions in PtP amplitudes of LEPs starting one to two hours postadministration and maintained for more than six hours postdose [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Treatment with ASP9226 (30 mg or 50 mg), compared with placebo, did not produce a difference greater than the 2.5 µV criteria that was predefined as the minimal clinically meaningful reduction in LEP N2-P2 PtP. However, treatment with pregabalin 150 mg showed differences vs placebo in LEP N2-P2 PtP amplitudes well above 2.5 µV, consistent with previous findings in healthy subjects [ 13 ], and confirmed the validity of the study design and method. In keeping with LEP results, subjects treated with pregabalin reported significantly lower postlaser VAS pain ratings compared with either dose of ASP9226 or placebo.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations